Hemodynamic Response in a Geographical Word Naming Verbal Fluency Test - Marino, Julián Carlos (2014)
Functional hemodynamic response was studied in a new Verbal Fluency Task (VFT) that demanded the production of geographical words while fMRI data was obtained. Participants completed 7 trials with a total duration of 2 min. 20 s. Four simple arithmetic subtraction trials were alternated with 3 geographical naming trials. Each trial had a duration of 20 s. Brain activity was contrasted between both conditions and significant differences (p < .05, Family Wise Error correction) were observed in the prefrontal medial gyrus, typically associated with word retrieval and phonological awareness, and in the parahippocampal gyrus, posterior cingulate cortex and lingual gyrus, areas related to spatial cognition. These results indicate that geographic VFT could be incorporated into a browser of cognitive processes using VFT considering its specific relationship with spatial cognition. Further investigations are proposed, taking special interest in the gender variable and eliminating phonological restrictions, because the evoked Argentinean cities and towns ended in a consonant letter.